Integration of Qur'an in mathematics learning - Kasman Kasman; Baharullah Baharullah; Andi Husniati (Universitas Ahmad Dahlan, 2025)
This study aims to identify and explain relevant verses of the Qur'an to be integrated into mathematics learning. We used a systematic literature review method to identify and to analyze previous studies. In this study, we collected relevant articles and then the articles were analyzed using a qualitative approach based on a content analysis. We successfully selected 10 research articles on the integration of the Qur'an verses in mathematics learning. The results of the study revealed that many mathematical concepts such as numbers, sets, geometry, sequence, logic, social arithmetic, and linear equation in one variable were found to be relevant to some Qur'an verses. Integrating the Qur'an in mathematics learning can foster students’ learning motivation and characters, such as obedient, fair, honest, and religious. It confirms that connecting mathematics with Islamic context not only enriches the learning process, but also fosters positive values in students and creates a more meaningful learning experience.